INTEGRATED NATIONAL IDENTITY STORAGE SECURITY SYSTEMS WITH BLOCKCHAIN TECHNOLOGY - Zaini Fathiyana, Rana
One of the prerequisites for the implementation of good governance is that each citizen has a single and unique population identity. However, the current condition of the information system developed by the issuing agency of national identity numbers is not integrated. Around 29 agencies recorded population data and issued different identification numbers. In the process of its application, there are several problems such as replication and data redundancy so that the possibility of committing crimes against citizens' identity data appears. Besides, the Government of Indonesia through the Ministry of Home Affairs is currently conducting a program to utilize population data for public services, by providing access to institutions that have collaborated in utilizing population data. In the application process, each identity issuing agency stores its citizens' identity data using a centralized system. There is a weakness in this centralized system that is the potential for data to be changed unilaterally and dependence on Dukcapil as a provider of basic identity data services for citizens. In this study, the proposed solution to overcome these problems is to use a distributed blockchain technology system. In this research, we discussed how to design a national identity data storage security system integrated with blockchain technology and implement it through the Hyperledger framework. Based on the test results, the system successfully fullfill 100% of test-case and the system is able to accommodate 1,814,400 transactions per day. This research proves that blockchain technology can support the implementation of the integration of national identity data and improve the security of citizens' identity data.